How Do Dental Students Determine Patients' Caries Risk Level Using the Caries Management By Risk Assessment (CAMBRA) System?. Issue 3 (1st March 2015) - Doméjean, Sophie; Léger, Stéphanie; Rechmann, Peter; White, Joel M.; Featherstone, John D.B.
Abstract : Research has demonstrated the validation of specific caries risk assessment (CRA) systems, but little is known about how dental practitioners assign a caries risk level to their patients. The aim of this study was to explore dental students' decision making in caries risk assignment when using the Caries Management By Risk Assessment (CAMBRA) system. Multiple correspondence analysis and chi‐squared automated interaction detector analysis were performed on data collected retrospectively for a period of six years (2003–09) at the University of California, San Francisco predoctoral dental clinic. The study population consisted of 12, 952 patients from six years of age through adult who received a baseline CRA during the period, were new to CAMBRA, and had not received any prior CAMBRA recommendations. The results showed variation in decision making and risk level assignment, illustrated by the range of percentages for the three scores (low, moderate, and high/extreme caries risk) when CRA was assigned for the first time. For those first‐time CRAs, decision making was mainly based on four factors: cavities or caries lesions into dentin on radiograph, restorations during the last three years due to caries, visible heavy plaque, and interproximal lesions into enamel (by radiographs). This study's findings provide important data regarding one group of CAMBRA users and thus contribute to the development of knowledge about the implementation of caries risk assessment in contemporary dental practice.